Sistem Pendukung Keputusan Pemilihan Kategori Skripsi Bagi Mahasiswa Sistem Informasi - Renny Puspita Sari; Enricho Rasimin (Jurnal Sistem Komputer dan Informatika (JSON), 2021)
SPK or usually called the Decision Support System is a system for recommending decisions using data, at Tanjungpura University, Faculty of Mathematics and Science, more precisely is Information Systems, which is now has more than 200 students where students are there still often confused to lift the title of what thesis they want, therefore I will create a system that can recommend what thesis is better used in this Information Systems study program using the SAW method, so that students can find out what thesis category is suitable for these students. Because the system uses course scores as data to make decisions, the accuracy of the system can exceed 90%.